Recent Advances in Smart Hydrogel for Drug Delivery in Cancer Therapeutics - Patkar, Smit Vijay; Sherje, Atul (Indian Journal of Pharmaceutical Education and Research, 2025)
Cancer has been listed as the world's second-leading cause of death. Even with the significant progress made in recent years, advanced stages of the disease are still incurable. Conventional treatment options, such as surgery, chemotherapy and radiotherapy, have several inherent drawbacks that result in severe side effects and poor therapeutic efficacy. These drawbacks include their limited applicability, low bioavailability, multidrug resistance and high recurrence. Three-dimensional networks of natural or synthetic polymers, known as hydrogels, have special qualities like biocompatibility, elasticity, porosity, permeability, softness and similarity to soft biological tissues. By enabling controlled drug release and lowering non-targeted exposure, hydrogel-based drug delivery systems have demonstrated improved results in minimizing side effects in recent times. Smart hydrogels that may react to environmental stimuli, such as changes in pH, redox, enzyme levels, temperature, light, shear/strain and so on, to alter their structure and properties. The present review highlights the basics of hydrogels and recent developments in their applications for targeted delivery of anticancer medications.
Keywords: Cancer therapeutics; Hydrogel; Smart hydrogel; Stimuli-responsive hydrogel